Analysis of the Distribution of Inheritance for Widows According to the Civil Code - Andri Wiranata; Sri Iin Hartini; Yulianus Pabassing (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2026)
Regulations regarding inheritance law cannot be separated from regulations regarding marriage law. This can be attributed to at least two factors: first, the process of determining heirs begins with marriage. In inheritance law, a widow is defined as a wife who outlives her spouse in a marriage that ends due to the death of her husband. This study aims to determine the position of widows as heirs according to the Civil Code and the distribution of inheritance for widows according to the Civil Code. The research method used in this study is normative legal research or library legal research, namely legal research conducted by conducting research on library materials or secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. These materials are then systematically compiled, reviewed, and conclusions are drawn in a summary with the problem being studied, namely inheritance for widows according to the Civil Code. The results of the study indicate that the position of widows as heirs is included in Class I of heirs. Based on the position of widows as heirs, Class I, widows inherit based on their own position. The widow's position appears as an heir based on priority, thus closing off other groups. A widow can inherit the inheritance by leaving parents, siblings, if there are no descendants who have the right to inherit. The distribution of inheritance for widows is based on Article 852a of the Civil Code; the widow's share of inheritance is equal to the share of a legitimate child, so that inheritance is head of household. A widow will receive ½ (half) of the joint property, and the remaining ½ (half) becomes the inheritance of the testator, which will be divided between the widow and her children.